Digital leadership in business organizations: an overview - Lizio Marcel de Araujo; Sidik Priadana; Vip Paramarta; Denok Sunarsi (Har Press Indonesia, 2021)
The main aim of this report is to identify and describe the idea of digital leadership. For the study, the effects of digital leaders' traits and experience on the digitalization process will be examined. Different multinational and global businesses have been examined to apply the concept of digital leadership to their businesses. In this paper, with the goal of an organizational literature review, we analyze the concept of digital leadership. The paper seeks to identify the digital leadership concept; to analyze these abilities and their impacts deeply in the new digital age. As a result of detailed literature research, digitalization and technological developments lead businesses to transform organizational structures, processes, business models, and strategies. Digital leadership is crucial for organizations to survive in the new digital era by adapting and transforming business strategies. To accomplish business objectives and successfully drive the digital business transformation, digital leaders use and enhance the company's digital assets. Digital leaders have different abilities and perspectives compared to traditional leaders. However, many organizations do not understand digital leaders' value, leading to poor performance and unrecoverable failures. This research paper demonstrates a strong link between digital leadership and corporate success and productivity, following the analysis and clarification of the digital leadership concept generated in the modern age and the review of variable business strategies and positioning of the leadership concept in different sectors.